Structure determination of fatty acid ester biofuels via in situ cryocrystallisation and single crystal X-ray diffraction. Issue 1 (5th December 2018) - Prathapa, Siriyara Jagannatha; Slabbert, Cara; Fernandes, Manuel A.; Lemmerer, Andreas
Abstract : In situ cryocrystallisation enabled the crystal structure determination of a homologous series of low-melting n -alkyl methyl esters C n −1 H2 n +1 CO2 CH3 . Abstract : In situ cryocrystallisation in combination with a zone-melting technique enabled the crystal structure determination of a homologous series of low-melting n -alkyl methyl esters C n −1 H2 n +1 CO2 CH3, from methyl pentanoate ( n = 5) to methyl tridecanoate ( n = 13), by single crystal X-ray diffraction. Two isostructural groups were identified: the odd-numbered triclinic members (C9, 11, 13 ) and the even-numbered orthorhombic members (C8, 10, 12 ). All observed structural trends, similarities and differences in intermolecular contacts, including the odd–even effect observable in melting point behaviour and unit cell parameters, were easily visualised and described by 2D fingerprint plots generated from the calculated Hirshfeld surfaces, in combination with atom–atom Coulomb–London–Pauli (AA-CLP) lattice energy calculations.